(untitled) (Ágora Journal, 2021)
The present paper has the main purpose of analyzing the role of captains-mores in military matters in the old Captaincy of Porto Seguro from 1670 to 1682, as well as the impact of the actions on the experience of the Indians and colonists. Seeking to understand in this way how the recruitment of these officers was, the possibilities of mobility among agents, as well as their promotion mechanisms. Thus, it is possible to reconstruct the profile and the socio-political and economic insertion of these officers, analyzing the forms of social reproductions through which they sought a better position within colonial society. The information found in different groups of documents went through the methodology of the indictment method to understand the small traces left by these individuals and the nominative links, to understand the relationships established by these subjects from the names that surround them, both developed by Micro-History. Thus, making it possible to know some of the strategies outlined by these individuals, influencing them to be seen and remain as men in charge. Finally, it is necessary to understand a locality from the specifics of its time and with that the appointments to the positions of captains-mores met these requirements, with relations based on greater interests, an example of this and the case of some ascension to the post of the captain. Captain-General, based on conflicts and intrigues.